Strategi Kepala Madrasah Dalam Meningkatkan Mutu Pendidikan - Adi Wibowo; Ahmad Zawawi Subhan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This article aims to describe the strategy of the headmaster in improving the quality of education starting from planning, implementation, monitoring to evaluation. To achieve these objectives, this study uses a qualitative approach with descriptive methods. Data collection techniques are done through Observation, Interview and Documentation Study. Data analysis procedures are Data Reduction, Data Servicing, and Verification. While the subject of research is the Head of Madrasas, Deputy Head of Madrasas, and Teachers. The object of this research is in Mts Negeri 1 Purworejo, data are taken before the covid pandemic 19. The results of the study show that: (1) that the headmaster in improving the quality of education first plans the program by detailing the needs of educators and education personnel who will carry out their tasks, plan curriculum to be implemented, planning policies on adding subjects; (2) create an organizational structure that involves parents through the school committee and completes the required sarpras; (3) Give a good and calm example at work, motivate and reward personnel both morally and materially, improve welfare, include educators and education personnel in education and training and motivate senior teachers to have the spirit of life long education; (4) supervise the outputs, PBM, and students starting from the admission process until the completion of school at the madrasah. (5) As for the obstacles experienced are the presence of personnel who are still undisciplined, the lack of communication between the madrasa head and some personnel.